Architectural Symbols of Chinese Three – Tiered Stage Pleasant Sound Pavilion - Petcharapiruch, Sasiporn (Journal of Sinology (วารสารจีนวิทยา), 2008)
The “three-tiered stage” or chóngtái sāncéng 崇臺三層 was an innovation of Chinese theatrical architecture during the Qianlong 乾隆 reign (1736–1796), a heyday of court theater in the Qing dynasty. The Qianlong emperor commissioned the construction of four such gigantic theaters, of which three are no longer extant. The only one still in existence is the three-tiered stage Pleasant Sound Pavilion (Chàngyīn Gé 暢音閣) in the Forbidden City. This three-tiered stage reflects an ingenuity of the Qing court theater. By focusing on this three-tiered stage, this study aims to use the only extant three-tiered stage Pleasant Sound Pavilion as a way to understand traditional Chinese architectural symbols embedded in its exterior structure and interior design.